GERAKAN LAWAN COVID-19 DENGAN PRODUKSI MANDIRI “HANSKI” MELALUI PEMBERDAYAAN KADER KESEHATAN DI BENGKULU - Widelia, Putri; Marlin, Leni; Sunita, Sunita; Susiwati, Susiwati; Halimatussa'diah, Halimatussa'diah (Poltekkes Kemenkes Bengkulu, 2024)
Coronavirus Disease 2019 or Covid-19 is a new type of virus whose transmission can occur between humans and humans. The Covid-19 pandemic was declared by WHO on March 9 2020, which is the biggest impetus for implementing this service program immediately. Vaccines or official treatments are still in the process of being developed and clinically tested to fight Covid-19, so the public must be able to take precautions by breaking the chain of spread of the virus through understanding and implementing health protocols in accordance with government recommendations. The government's recommendation is to adopt a clean lifestyle by washing your hands with soap or using hand sanitizer, keeping your distance, using a mask when outside the house and staying at home. This government recommendation has resulted in the scarcity of availability of hand sanitizers and the selling price has also increased due to mass consumption. Based on these problems, the community service team carried out community service activities in the form of assisting cadres in Pondok Kelapa District in making hand sanitizer made from basil as education for early prevention of Covid-19 in the Pondok Kelapa District, Central Bengkulu Regency. The aim of this service is to provide education to community cadres about how to make hand sanitizer made from basil. The method used is direct work practice on site in the form of providing material about Covid-19 and direct guidance or training in making hand sanitizers for Pekik Nyering Community Health Center cadres which is a work area in Pondok Kelapa District and distributing basil seeds. The results of this community service activity show the high enthusiasm and activeness of all participants. All cadres succeeded in practicing making hand sanitizer and even made excess to give to other colleagues.Keywords: Hand sanitizer, Basil, Cadre